Estado digital: Para entender o estado como plataforma - Tulio Chiarini; Alexandre Arns Gonzales (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– In the context of the digital transformation of the state, this Discussion Paper aims to analyze the literature on the "Government as a platform" (GaaP). A common point in this bibliography is the reference to Tim O'Reilly's 2011 essay, which proposed lessons that the public sector could learn from the experiences of digital platform companies. To this end, a semi-systematic approach to the literature review was adopted, with searches using specific terms and Boolean operators in the Web of Science databases (including SciELO) and Cairn.info. The search resulted in 67 references, of which 33 directly address GaaP. The analysis of this literature revealed a concerning trend toward the naturalization of the logic of large digital platforms, suggesting that the concept of GaaP is linked to an agenda of privatizing public services and policies, marked by the adoption of digital products and services by the public sector. The literature also highlights the central role of digital data from public services and policies in this transformation, while discussing little about the ownership regime, development, and use of the technologies that give material form to the GaaP. A rhetoric focused on reducing the state and fiscal austerity is evident, and social and citizen participation in the formulation and delivery of public services is often confused with the dynamics of data extraction. As a final consideration, we suggest future research agendas to deepen the debate on the concept of GaaP and digital transformation.
Keywords: O33; O39; H11; 330; government platformization; government as a platform; government digital transformation